Effect of Diameter of Teak Stump on Survival and Height Growth - Griffith, A. L. (Indian Forester, 1947)
The Central Silviculturist has sent us the following further account of the experiments started in 1943 and 1944 in the Boni forests by the divisional forest officer, Hoshangabad on the effect of the diameter of teak stumps on survival percentage and height growth. The experiments are of interest in that they confirm the results of the original experiments in Madras and also show that even after three growing seasons differences are still significant. The results are very striking and very important in the early competition of a plantation against weeds. An account of these experiments appeared at pages 329-331 of the Indian Forester of October 1945.